Clarke's alpha, beta and zero components: A possible approach for the conceptual design of instrumentation compatible with IEEE Std. 1459-2000 - Emanuel, Alexander Eigeles; Milanez, Dalgerti Lelis [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2004)
The paper explains the conceptual design of instrumentation that measures electric quantities defined in the trial-use Std. 1459-2000. It is shown how the Instantaneous-Space-Phasor (ISP) approach, based on α, β, 0 components, can be used to monitor electric energy flow, evaluate the utilization of transmission line and quantify the level of harmonic pollution injected by nonlinear loads.
Keywords: Power Measurements; Power Quality; Powers Definitions; Akagi's method; Dynamic compensators; Power definitions; Power quality; Computational methods; Electric lines; Electric power measurement; Energy utilization; Nonlinear systems; Standards; Vectors; Instrument components